The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1600-051x.1993.tb00773.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between crown form and clinical features of the gingiva in adolescents

Abstract: The purpose of the present study was to examine the relationship between the form of the crowns in the maxillary front tooth segment and (1) a group of morphological characteristics and (2) the thickness of the gingiva. 108 subjects devoid of symptoms of destructive periodontal disease were examined regarding, e.g., probing depth, thickness of the free gingiva, width of the keratinized gingiva and the contour of the marginal gingiva. From clinical photographs of the maxillary front tooth region, the width (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
230
8
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(297 citation statements)
references
References 16 publications
24
230
8
11
Order By: Relevance
“…5 In the present study the periodontal probing depth was associated with thicker gingiva among the cases, which was in accordance with observations made by several other authors who also reported that subjects with a thick periodontal phenotype had on an average higher mean periodontal probing depth. 19,20,21 However, such a correlation between the probing depth and gingival thickness did not exist in the control group.…”
Section: Discussionmentioning
confidence: 82%
“…5 In the present study the periodontal probing depth was associated with thicker gingiva among the cases, which was in accordance with observations made by several other authors who also reported that subjects with a thick periodontal phenotype had on an average higher mean periodontal probing depth. 19,20,21 However, such a correlation between the probing depth and gingival thickness did not exist in the control group.…”
Section: Discussionmentioning
confidence: 82%
“…Susceptibility to recession may be influenced by the position of the teeth in the arch, the root-bone angle, and the mesiodistal curvature of the tooth surface [54], [55]. Moreover, there is also evidence suggesting that thin gingival tissue (thin biotype/phenotype) is more prone to recession [56], [57]. Many authors have hypothesized that on rotated, tilted, or facially displaced teeth, the bony plate is thinned or reduced in height.…”
Section: Gingival Recession In Orthodontics: a Reviewmentioning
confidence: 99%
“…Patients with thin periodontium are shown to have long narrow maxillary central incisors, whereas patients with a thick biotype have short and wide central incisors. 28 In addition, the thick periodontal biotype has a thick osseous structure with flat morphology and a thick gingival tissue with short wide papilla. Thick biotype is associated with less open embrasures especially around implants.…”
Section: Periodontal Disease and Open Gingival Embrasuresmentioning
confidence: 99%